Analisis Formulasi Visi, Misi, dan Tujuan Institusi: Studi Kasus Madrasah Ibtidaiyah (MI) Manba’ul Huda - Sulastri, Asri; Hidayat, Ahmad Saiful; Badrudin, Badrudin (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2024)
Madrasah Ibtidaiyah (MI) is a primary level Islamic education institution that has an important role in shaping children's character and morals. important role in shaping the character and morals of children. The formulation of vision, mission, and goals of MI is a key step in determining the direction and focus of education in this institution. This researchaims to understand the process of formulating vision, mission and goals in MI and its impact on curriculum development and school policies. On curriculum development and school policies. The research methodology involved interviews with principals, teachers and relevant stakeholders at MI Manba'ul Huda. Results the results show that the formulation of MI vision involves various parties and involves aspects such as Islamic values, local needs, and global developments. MI mission tends to instill Islamic values. The objectives of MI include improving the quality of learning quality, Islamic character building, and preparing students for a better life better life.